Changes in suicide in California from 2017 to 2021: a population-based study - Julia J. Lund; Elizabeth Tomsich; Julia P. Schleimer; Veronica A. Pear (BMC, 2023)
Abstract Background Suicide is a major public health problem with immediate and long-term effects on individuals, families, and communities. In 2020 and 2021, stressors wrought by the COVID-19 pandemic, stay-at-home mandates, economic turmoil, social unrest, and growing inequality likely modified risk for self-harm. The coinciding surge in firearm purchasing may have increased risk for firearm suicide. In this study, we examined changes in counts and rates of suicide in California across sociodemographic groups during the first two years of the COVID-19 pandemic relative to prior years. Methods We used California-wide death data to summarize suicide and firearm suicide across race/ethnicity, age, education, gender, and urbanicity. We compared case counts and rates in 2020 and 2021 with 2017-2019 averages. Results Suicide decreased overall in 2020 (4123 deaths; 10.5 per 100,000) and 2021 (4104; 10.4 per 100,000), compared to pre-pandemic (4484; 11.4 per 100,000). The decrease in counts was driven largely by males, white, and middle-aged Californians. Conversely, Black Californians and young people (age 10 to 19) experienced increased burden and rates of suicide. Firearm suicide also decreased following the onset of the pandemic, but relatively less than overall suicide; as a result, the proportion of suicides that involved a firearm increased (from 36.1% pre-pandemic to 37.6% in 2020 and 38.1% in 2021). Females, people aged 20 to 29, and Black Californians had the largest increase in the likelihood of using a firearm in suicide following the onset of the pandemic. The proportion of suicides that involved a firearm in 2020 and 2021 decreased in rural areas compared to prior years, while there were modest increases in urban areas. Conclusions The COVID-19 pandemic and co-occurring stressors coincided with heterogeneous changes in risk of suicide across the California population. Marginalized racial groups and younger people experienced increased risk for suicide, particularly involving a firearm. Public health intervention and policy action are necessary to prevent fatal self-harm injuries and reduce related inequities.